Flu Vaccine and Mortality in Hypertension: A Nationwide Cohort Study - Daniel Modin; Brian Claggett; Mads Emil Jørgensen; Lars Køber; Thomas Benfield; Morten Schou; Jens‐Ulrik Stæhr Jensen; Scott D. Solomon; Ramona Trebbien; Michael Fralick; Orly Vardeny; Marc A. Pfeffer; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Influenza infection may increase the risk of stroke and acute myocardial infarction (AMI). Whether influenza vaccination may reduce mortality in patients with hypertension is currently unknown. Methods and Results We performed a nationwide cohort study including all patients with hypertension in Denmark during 9 consecutive influenza seasons in the period 2007 to 2016 who were prescribed at least 2 different classes of antihypertensive medication (renin‐angiotensin system inhibitors, diuretics, calcium antagonists, or beta‐blockers). We excluded patients who were aged <18 years, >100 years, had ischemic heart disease, heart failure, chronic obstructive lung disease, cancer, or cerebrovascular disease. The exposure to influenza vaccination was assessed before each influenza season. The end points were defined as death from all‐causes, from cardiovascular causes, or from stroke or AMI. For each influenza season, patients were followed from December 1 until April 1 the next year. We included a total of 608 452 patients. The median follow‐up was 5 seasons (interquartile range, 2–8 seasons) resulting in a total follow‐up time of 975 902 person‐years. Vaccine coverage ranged from 26% to 36% during the study seasons. During follow‐up 21 571 patients died of all‐causes (3.5%), 12 270 patients died of cardiovascular causes (2.0%), and 3846 patients died of AMI/stroke (0.6%). After adjusting for confounders, vaccination was significantly associated with reduced risks of all‐cause death (HR, 0.82; P<0.001), cardiovascular death (HR, 0.84; P<0.001), and death from AMI/stroke (HR, 0.90; P=0.017). Conclusions Influenza vaccination was significantly associated with reduced risks of death from all‐causes, cardiovascular causes, and AMI/stroke in patients with hypertension. Influenza vaccination might improve outcome in hypertension.